An Artificial miRNA against HPSE Suppresses Melanoma Invasion Properties, Correlating with a Down-Regulation of Chemokines and MAPK Phosphorylation - Liu, Xiaoyan; Fang, Hong; Chen, Hongchao; Jiang, Xiaoling; Fang, Deren; Wang, Yan; Zhu, Dingxian (PLOS ONE, 2012)
Ribonucleic acid interference (RNAi) based on microRNA (miRNA) context may provide an efficient and safe therapeutic knockdown effect and can be driven by ribonucleic acid polymerase II (RNAP II). In this study, we designed and synthesized miR155-based artificial miRNAs against heparanase (HPSE) constructed with BLOCK-iT™ Pol II miR RNAi Expression Vector Kit. The expression levels of HPSE declined significantly in both the mRNA and protein levels in HPSE-miRNA transfected melanoma cells that exhibited reduction of adhesion, migration, and invasion ability in vitro and in vivo. We also observed that HPSE miRNA could inhibit the expressions of chemokines of interleukin-8 (IL8) and chemokine (C-X-C motif) ligand 1 (CXCL1), at both the transcriptional and translational levels. Further study on its probable mechanism declared that down-regulation of IL8 and CXCL1 by HPSE-miRNA may be correlated with reduced growth-factor simulated mitogen-activated kinase (MAPK) phosphorylation including p38 MAPK, c-Jun N-terminal kinase (JNK) and extracellular-signal-regulated kinase (ERK) 1 and 2, which could be rescued by miRNA incompatible mutated HPSE cDNA. In conclusion, we demonstrated that artificial miRNAs against HPSE might serve as an alterative mean of therapy to low HPSE expression and to block the adhesion, invasion, and metastasis of melanoma cells. Furthermore, miRNA-based RNAi was also a powerful tool for gene function study.